Restoration of the molecular clock is tumor suppressive in neuroblastoma - Myrthala Moreno-Smith (Nature Portfolio, 2021)
MYCN is frequently amplified in neuroblastomas. Here, the authors show that MYCN disrupts the molecular clock by downregulating clock activator RORα and that the reactivation of RORα restores BMAL1 activity, and inhibits lipid metabolism and neuroblastoma growth